Polypoidal choroidal vasculopathy in a patient with early-onset large colloid drusen - Giovanna Vella (American Journal of Ophthalmology Case Reports, 2021)
Purpose: To report a case of a 46-year-old patient affected by polypoidal choroidal vasculopathy (PCV) in large colloid drusen (LCD) and to show how switching to intravitreal injection of aflibercept could be considered as a useful treatment of PCV not responsive to other anti-vascular endothelial growth factor (VEGF) injections. Observations: A 46-year-old woman was referred to our department with diagnosis of early-onset retinal drusen. Multimodal imaging confirmed the diagnosis of LCD in both eyes, complicated by suggestive PVC in the left eye. Due to the absence of anatomical improvement after 6 intravitreal injections of ranibizumab, the patient was switched and treated by a single injection of aflibercept, showing a complete anatomical and functional recovery. Conclusions and Importance: This case suggests progressive development of PCV as a possible late evolution of degenerating LCD. In case of exudative complication, intravitreal aflibercept injection could be considered as a useful treatment, especially in patients who are not responsive to others anti-VEGF injections.